C3b receptors on human glomeruli in vitro. Loss in culture. - Scheinman, J. I. (1978)
C3b receptors, easily demonstrated on isolated human infant glomeruli, are lost as cells grow in culture. This suggests that epithelial cells are dedifferentiated or that the C3b receptor is not intrinsic to the epithelial cell.